Development of Technical Education in Colonial India: A Historical Overview - Doley, Debobrat (International Journal of Control and Automation, 2019)
Technology is touching every aspect of life and society. Since Independence, the technical education system in our country has grown into a fairly large-sized system, offering opportunities for education and training in a wide variety of trades and disciplines at a certificate, diploma, degree, postgraduate degree and doctoral levels in institutions located throughout the country.The general scenario of higher education in India is not equivalent with the global quality standards. Hence, there is enough justification for an increased assessment of quality of the country’s educational institutions. In order to maintain the standard of technical education, The All India Council for Technical Education (AICTE) was set up in 1945. AICTE is responsible for the planning, formulation and maintenance of norms and standards, quality assurance through accreditation, funding in priority areas, monitoring and evaluation, maintaining parity of certification and awards and ensuring coordinated and integrated development and management of technical education in the countr